An Examination of the Quality of Social Sciences Journals Published in Nigeria: Implications for Collection Development. Issue 3 (1st October 2017) - Ezema, Ifeanyi J.; Ugwu, Cyprian I.; Asogwa, Brendan Eze
Abstract: This study was conducted to examine the quality of Social Science journals published in Nigeria using document analysis of the editorial policy as found in the journals used for the study in addition to Google search of the web visibility and impact of the journals. Twenty five social science journals in Nigeria which were subscribed by University of Nigeria Library from 2005 to 2014 were used for the study, but four of the journals that have no relevant information required for the study were excluded leaving only 21 journals used for analysis. Web citations of the journals were obtained to determine their visibility and impacts. Findings show that the editorial boards of majority of the journals were composed of professors and doctorate degree holders. It was also found that more than 60% of the journals are published biannually; however, a few journals are indexed internationally. The common citation pattern of the journals is APA style, while 9.5% of the journals have web presence. All the journals examined publish in English language while only one of them publishes in other language. Findings also reveal that commercial publishers are dominant in the establishment of the journals; only 19.04% of them are published by professional bodies. This study is useful guide for researchers, librarians, academic institutions and professional associations in establishment and selection of journal for scholarly communication in the Social Sciences.